The prediction of elastic modulus in sheet-reinforced composites using a homogenization approach - Xiaoxia Zhai; Huzaifa Hashim; Jun Huang; Soo, Eugene Zhen Xiang (MDPI, 2025)
Based on the equal-stress formula and equal-strain formula of material mechanics, a new formula for predicting Young’s modulus of sheet-reinforced composite is derived by taking sheet-graphene composite as an example. The effectiveness of the formula is verified by comparing it with the mixing rate (ROM), Halpin–Tsai equation, and finite-element simulation. This formula is used to discuss the effect of interface-layer properties on the modulus of composite materials. Compared with the case without interface, when the graphene content is 3% and the interface-layer properties are linearly distributed and exponentially distributed, respectively, the embedded RVE modulus prediction increases by 5.06%, and the sandwich RVE modulus prediction increases by 56.5% and 31.75%, respectively. The influence of the change in interface-layer thickness from 0 to 1.5 nm (determined according to the existing literature) is also discussed. The predicted modulus of embedded RVE and sandwich RVE increases by 73% and 11.3%, respectively. The results show that the influence of the thickness and properties of the interface layer on the modulus prediction of graphene composites cannot be ignored. Combined with the analysis of experimental data, it is found that the experimental data fall within the prediction range of the modulus of the formula, indicating that the formula can be used for the preliminary trend analysis of the mechanical test of graphene-composite materials in the early stage, saving testing costs and time.